Qualitative and quantitative study of algae in three drinking water plants supply springs in Sulaymaniyah province - Kurdistan region of Iraq - Bashar T. I. AL-Shandah; Riadh Abas Abd Al-Jabar; Trifa K. J. Farkha (Tikrit Journal of Pure Science)
In this study, three drinking water treatment plant supply springs were selected within different sites in Sulaymaniyah province- Kurdistan region of Iraq. Samples were collected over period of eight months from May to the end of December 2015.